De paramarkt: New Age en volksgeloof - Frans Jespers (Religie & Samenleving)
In the Netherlands, the paranormal circuit is rather visible in the ‘paranormal fairs’ for the last twenty years. Sociologists consider such fairs as commercialized New Age practices, but I doubt if they are identical. In my article, I summarize eight characteristics of New Age, and then I present a description of some paranormal fairs and the complete circuit around it. From that, I can deduce some remarkable differences between these fairs and New Age. At the fairs, people have a directly thaumaturgical expectation, especially when clairvoyants invoke assistant spirits. Visitors combine a more or less dualistic world view with practices from various religions (e.g. reincarnation, amulets). The majority of the visitors belongs to the (lower) working class. In conclusion, the paranormal fairs represent a special form of ‘the spiritual revolution’ (Heelas & Woodhead), namely New Age in its most popular and traditional version, hardly secularized, but quite reenchanting or re-sacralizing. In sum, the paranormal ‘market’ may show a take-over of a part of New Age by folk religion.